Ultrathin Metal Films with Defined Topographical Structures as In Vitro Cell Culture Platforms for Unveiling Vascular Cell Behaviors - Jun, Indong; Chung, Yong-Woo; Park, Jimin; Han, Hyung-Seop; Park, Jaeho; Kim, Saeromi; Lee, Hyunjung; Kim, Sang Hoon; Han, Jun-Hyun; Kim, Hyunjung; Seok, Hyun-Kwang; Kim, Yu-Chan; et al. (Wiley-Blackwell, 2016)
Implanted material surfaces make direct contact with body tissues to work on its own purpose. Therefore, studies of the surface properties of implantable materials that determine cell fate are very important for successful implantation. Although numerous studies have addressed the relationship between cells and material surfaces, nonmetallic surfaces and metallic surfaces likely produce different cellular responses because of their intrinsic differences in surface energy, roughness, and chemical composition. Moreover, given the nontransparent property of metal materials, which hampers the real-time imaging of cellular behavior, a detailed cellular-level analysis at the metal-tissue interface has not been performed. In this study, metal-based cell culture platforms (MCPs) with defined microscale topographical patterns are developed using a combination of photolithography and direct current magnetron sputtering techniques. The MCPs allow to observe vascular cells on metals in real time and identify the selective regulation of human aortic smooth muscle cells and Human umbilical vein endothelial cells (HUVECs) by metallic surface topography. Additionally, atomic force microscopy, contact angles, and energy-dispersive X-ray spectroscopy analyses show that the MCPs exhibit nearly identical chemical properties with their bulk counterparts, demonstrating that MCPs can be utilized as an in vitro cell culture platform system for understanding the cellular behavior on metal substrates.